50. MALOCCLUSION STATUS OF HIGH SCHOOL STUDENTS IN YEN CHAU DISTRICT, SON LA PROVINCE (Vietnam Journal of Community Medicine, 2024)
A cross-sectional study of 183 high school students, grade 10, from which the status of malocclusion and Spee curve was evaluated.Objects: Describe the malocclusion status of high school students in Yen Chau district, Son La province.Method: A cross-sectional study.Results: The malocclusion status of the study group: the highest proportion was type III (58%), followed by type II (30%). The difference in malocclusion by gender was not statistically significant (p > 0.05). The distribution of Spee curve level according to the rate of malocclusion was also not statistically significant according to this study. There was no difference in mean curve of Spee depth between malocclusion groups with p > 0.05.Conclusions: The study has provided additional figures for previous studies on malocclusion in Vietnam. The malocclusion in Yen Chau, Son La has differences compared to previous figures due to the unique characteristics of ethnicity and socio-economics.
Keywords: spee; malocclusion